DEVELOPMENT OF THE UKRAINIAN MUSIC THEATRE IN CANADA IN THE CONTEXT OF CULTURE DEVELOPING PROCESSES OF THE 20TH CENTURY - Karas’, H. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the Ukrainian music theater in Canada, which evolved from amateur theatricals of the genre art into opera productions at the professional level. If in the first half of the 20th c., there was dominance of musical and dramatic performances staged at numerous clubs and amateur theater groups, after World War II, the arrival of professional artists (singers, conductors) in the country caused the theatre to become professional. The creative activity of famous conductors L. Turkevych, V. Kolesnyk, M. Dyty-niak, singers M. Holynskyi, I. Hoshuliak, G. Kolesnyk, B. Chaplynskyi, M. Kokolska-Musiytchuk and others secured the staging of a number of musical performances and concerts on the American continent for the first time. This showed the high professional level of Ukrainian music as well as musical and dramatic art. It became an integral part of the multicultural palette of Canada, indicating its recognition.